Study of Failure of the Steam Tubes of Boiler Furnaces in Najebia Power Plant - Najim, Saleh E.; Mohammed, Haider M. (Basrah Journal for Engineering Sciences, 2011)
Failures in the steam tubes of boiler furnaces in Najebia power plant was studied experimentally. Visual examination, mechanical tests, microscopic test and chemical analyses were performed. Visual examination showed the types of failure in the tubes. Tensile and hardness tests were performed to estimate the variation in the mechanical properties of the tubes metal and compared with the new tubes. Microscopic test for the failed tubes used to recognize the difference in the microstructure to the metal of the tubes. Chemical analyses involved chemical composition of the tubes metal, river and feed water analyses, water treatment, fuel analyses and analysis of deposits and oxides on the external and internal sides. Overheating and wall thinning of the tubes resulted from oxygen escaping to the inner side of these tubes, and presence of deposits and oxides on the external and internal sides which led to failure was studied extensively. Engineering remedies were also given to confine the problem and to prevent it in future.